Transportation costs are particularly high, representing a significant portion of logistics costs alongside warehousing, Cambodia’s Regional Connectivity, Unlocking the full Potential of Transport Corridor - Ratha Long; Dr. Chanthy Sin; Sou Lalin; Mr Seng Vithou; Dr. Sam Chamreun (International Journal of Multidisciplinary Research and Studies, 2026)
Cambodia’s logistics sector continues to face significant cost pressures, with transportation and warehousing accounting for a large share of total logistics expenses. Despite ongoing investments in transport corridors and regional connectivity initiatives, logistics costs in Cambodia remain higher than those of neighboring countries, reducing the competitiveness of domestic exporters and limiting integration into regional value chains. This study examines the underlying drivers of high transportation and warehousing costs, including infrastructure constraints, customs procedures, market fragmentation, and limited logistics service capacity. Using a mixed-methods approach that combines secondary data analysis with field insights from exporters and logistics providers, the research assesses both the structural and operational factors shaping logistics performance. The findings highlight persistent bottlenecks that elevate transport costs and identifies reform areas with high potential impact, particularly in corridor upgrades, customs simplification, and warehouse efficiency improvement. The study provides evidence-based policy recommendations aimed at reducing logistics costs, enhancing trade competitiveness, and supporting Cambodia’s long-term economic growth DOI:- 10.5281/zenodo.19082413